Sclerosus and atrophic genital Lichen or vulvar craurosis. About a case - Graciela Caridad Cabrera Acea; Julia M. Hernández Mompié; Cynthia Gómez Cabrera (Medisur, 2016)
Sclerosus and atrophic genital Lichen or vulvar craurosis is an affection characterized by a progressive chronic atrophy of the vulvar skin and mucosa, associated to involutive changes in external genitalia. The presentation of this case was motivated by the unusual appearance of it in our context. A 49 year old white patient with history of hypertension, came to the Dermatology consultation referred by her Family Doctor. She reported that she had had an intense pruritus since approximately eight months in the vulvar region and changes in texture which she stated as ¨hardening sensation¨ which had had intensified, so as irregularities in her menstrual period, all of which was not relieved with the usual treatment as it was interpreted as vaginal parasites. She explained that she suffered from an intense pain during intercourse, more frequently in the last months so as sleeping problems and nervousness. A biopsy was performed and it showed lichen sclerosus. It was treated with local high potency steroids, conjugated estrogens and psychological support. The patient had an evident symptom improvement. She has a periodic evaluation to avoid relapse and /or complications.